STUDENT LEARNING OUTCOMES DURING DISTANCES LEARNING: THE ROLE OF EMOTIONAL INTELLIGENCE AND LEARNING DISCIPLINE - Seftiyana, Devi; Susanti, Santi; Fauzi, Achmad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This research aims to determine the effect of emotional intelligence and learning discipline on learning outcomes of spreadsheet subject at SMK Negeri 13 Jakarta. The population of this research was 108 students and the sample of this study was taken as many as 84 students with the sampling technique using Proportional Random Sampling. The technique of collecting data is through a questionnaire with a Likert scale and documentation. Based on multiple linier regression analysis technique, t test result show that emotional intelligence and learning discipline partially have a positive and significant effect on learning outcomes with t value < 0,05. Meanwhile, F test result show that emotional intelligence and learning discipline simultaneously have a positive and significant effect on learning outcomes with F significance < 0,05. The analysis of the coefficient of determination has an R Square value of 0.804, it means that emotional intelligence and learning discipline simultaneously have ability to explain students learning outcomes by 80,4%, while the remaining is influenced by unexamined variables.